A Study of English Program in Madrasah Aliyah Zainul Hasan Genggong Probolinggo - Zaimatus Sholehah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: English becomes the most used language in the world. Not every school has special program to improve students’ English proficiency especially speaking; however, MA Model Zainul Hasan Genggong provides English program for their students. The purpose of this program is to provide background knowledge for students and to allow students to practice speaking English. This study aimed to describe the English program of MA Model Zainul Hasan Genggong Probolinggo in the term of materials, implementation, and evaluation. Descriptive qualitative design was employed in this research. The subject was one of the English teachers of MA Model Zainul Hasan Genggong Probolinggo. The researcher used observation, interview, recording, and documents as the instruments. Then the qualitative data analysis was applied. The findings of this study showed that the materials of this program also need to be improved, such as providing guide book or hand book for students. And the implementation of English program runs well based on observation and interview. This program got positive responses from the students; they are enthusiastic in participating this program.